Comparative Analysis of Equivalent Material based on MFI - Mahesh Zope; Pratik Sonawane; Deepti Marathe (International Journal of Engineering and Management Research, 2021)
Polymers of the same family show distinct behavior with each other and because of this, the end prediction after molding the part is very difficult. Simulations result does not always match the product. For close substitution in absence of exactly known material composition, the equivalent grade of the same MFI may be used. However, the MFI is a poor indicator of the rheological behavior to be comprehend for accurate simulation. This research analyzes the appropriate parameters for the rheology of polymers, in the same class that are appropriate.